2013
DOI: 10.1002/chem.201302943
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Triple‐Layered Ag@Co@Ni Core–Shell Nanoparticles for the Catalytic Dehydrogenation of Ammonia Borane

Abstract: Triple-layered Ag@Co@Ni core-shell nanoparticles (NPs) containing a silver core, a cobalt inner shell, and a nickel outer shell were formed by an in situ chemical reduction method. The thickness of the double shells varied with different cobalt and nickel contents. Ag 0.04 @Co 0.48 @Ni 0.48 showed the most distinct core-shell structure. Compared with its bimetallic core-shell counterparts, this catalyst showed higher catalytic activity for the hydrolysis of NH 3 BH 3 (AB). The synergetic interaction between Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…As the y value increasing to 0.1, the catalyst showed the best activities that reaction time decreased to 7.5 min with maximum of hydrogen generation catalyzed by the Cu 0.4 @Co 0.5 Ni 0.1 NPs, the best proportion of the metal addition. The maximum hydrogen generation rate was 7340.80 mL min À1 g À1 more than many tri-metallic core-shell materials reported [31,35]. Therefore, the molar ratio of Cu: Co: Ni was 0.4:0.5:0.1 that formed the Cu 0.4 @Co 0.5 Ni 0.1 core-shell NPs, the best catalyst for the hydrolysis of AB.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…As the y value increasing to 0.1, the catalyst showed the best activities that reaction time decreased to 7.5 min with maximum of hydrogen generation catalyzed by the Cu 0.4 @Co 0.5 Ni 0.1 NPs, the best proportion of the metal addition. The maximum hydrogen generation rate was 7340.80 mL min À1 g À1 more than many tri-metallic core-shell materials reported [31,35]. Therefore, the molar ratio of Cu: Co: Ni was 0.4:0.5:0.1 that formed the Cu 0.4 @Co 0.5 Ni 0.1 core-shell NPs, the best catalyst for the hydrolysis of AB.…”
Section: Resultsmentioning
confidence: 97%
“…Compared to bimetallic catalysts, tri-metallic core-shells show the excellent performance with high hydrogen generation rate because of their extraordinary structure strengthening the synergetic interaction among the different components. Nevertheless, the reported tri-metallic coreshell structures consist of noble metals almost which severely restrain their practical application in the future [31]. For this reason, it's imperative to synthesis novel tri-metallic coreshell catalysts with non-noble metals and high catalytic performance in the meantime [29,32].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to alloy and monometallic counterparts, the Au@Co NPs exhibited excellent catalytic activity and long-term stability in the hydrolysis of AB. A similar approach was used to synthesize bimetallic Cu@M [74], Pd@M [75], Ag@M [76], and Ru@M (M = Fe, Co, Ni) [77] and trimetallic Au@Co@Fe [78], Cu@FeNi [79], Cu@CoNi [80], Cu@FeCo [81], Cu@CoCr [82], Ag@CoFe [83], Ag@NiFe [83], Ag@CoNi [84], and Ag@Co@Ni [85] core shell NPs. It was found that all the obtained bimetallic or trimetallic core-shell NPs showed higher activities than the corresponding monometallic counterparts in the hydrolysis of AB.…”
Section: Ammonia Boranementioning
confidence: 99%
“…In this work, template‐based electrodeposition process was employed to produce core–shell nanowires containing Ag, Co and Ni atoms. The literature contains extremely limited reports on synthesis and characterization of nano‐solids containing Ag, Co and Ni atoms (Yang et al ., ; Qiu et al ., ). In one study, Yang et al .…”
Section: Introductionmentioning
confidence: 97%